2014
DOI: 10.3329/dujbs.v23i2.20098
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of bari mung-5 (Vigna radiata L. Wilczek) following TIBA application

Abstract: An experiment was conducted to evaluate the effect of TIBA (0, 20, 50, 100, 150 mg/l) on the growth and yield attributes of BARI Mung-5 laid out in RBD. Plant height decreased due to TIBA treatments. Number of branches and leaves per plant were found to increase in all the treatments at all the ages of growth except at 7 DAS and the maximum number of branches and leaves were recorded due to 20 mg/l TIBA treatment. Dry matter per plant increased due to 20 mg/l TIBA in most cases and was significantly highest at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 5 publications
(5 reference statements)
7
18
0
Order By: Relevance
“…Stem diameter was also reduced except in the plants treated with 10 ppm TIBA where the diameter increased by 8.70% over the control. Similar results of decrease in plant height due to TIBA treatment have been reported in soybean (Jahan and Khan, 2014) and mungbean (Adam and Jahan, 2014). Tsegaw et al (2005) reported thicker stems due to growth retardant PBZ.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Stem diameter was also reduced except in the plants treated with 10 ppm TIBA where the diameter increased by 8.70% over the control. Similar results of decrease in plant height due to TIBA treatment have been reported in soybean (Jahan and Khan, 2014) and mungbean (Adam and Jahan, 2014). Tsegaw et al (2005) reported thicker stems due to growth retardant PBZ.…”
Section: Resultssupporting
confidence: 84%
“…Significantly lowest number of branches and leaves per plant were obtained due to 30 ppm TIBA treatment. Increase in number of branches and leaves per plant following TIBA application was reported by Adam and Jahan (2014) in mungbean. The present result is also in consistent with the findings of other investigators (Chung and Kim, 1989;Rahman and Rahman, 1997).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Length of panicle was also found to increase following both 50 and 100 ppm treatments but statistically similar to control. Increases in length of pods due to TIBA application were reported by Munira (2015) in BARI Maize-6 and Adam and Jahan (2014) in BARI Mung-5. However, Misra and Sahu (1958) did not find any significant changes due to TIBA application on rice plant.…”
Section: Resultsmentioning
confidence: 68%
“…Among the synthetic plant growth regulators, TIBA, a polar auxin transport inhibitor is widely used. At low concentration, it is capable of checking the excessive vegetative growth and lodging tendency, reducing the abscission of flowers and immature pods, and modifying the crop canopy to improve the productivity of crops (1) .…”
mentioning
confidence: 99%